2018
DOI: 10.1155/2018/8516285
|View full text |Cite
|
Sign up to set email alerts
|

Glycyl tRNA Synthetase (GARS) Gene Variant Causes Distal Hereditary Motor Neuropathy V

Abstract: Distal hereditary motor neuropathies (dHMN) are a rare heterogeneous group of inherited disorders specifically affecting the motor axons, leading to distal limb neurogenic muscular atrophy. The GARS gene has been identified as a causative gene responsible for clinical features of dHMN type V in families from different ethnic origins and backgrounds. We present the first cohort of family members of Nigerian descent with a novel heterozygous p.L272R variant on the GARS gene. We postulate that this variant is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…GARS has been associated with CMT2D and dSMA. Consistent with recent reports (Chung et al, ; Eskuri et al, ; James et al, ; Liao et al, ), our results suggest that GARS variants could potentially lead to early onset SMA‐like features depending on the nature and location of the amino acid change. Functional studies have shown that GARS consists of multiple domains including the catalytic, anti‐codon binding and dimerization domain, and mutations in each of these domains (Antonellis et al, ; Griffin et al, ) leads to axonal neuropathy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GARS has been associated with CMT2D and dSMA. Consistent with recent reports (Chung et al, ; Eskuri et al, ; James et al, ; Liao et al, ), our results suggest that GARS variants could potentially lead to early onset SMA‐like features depending on the nature and location of the amino acid change. Functional studies have shown that GARS consists of multiple domains including the catalytic, anti‐codon binding and dimerization domain, and mutations in each of these domains (Antonellis et al, ; Griffin et al, ) leads to axonal neuropathy.…”
Section: Discussionsupporting
confidence: 93%
“…Among the patients with dSMA, CMT2D, or infantile SMA and GARS variants published in the literature ( n = 45), we found that seven had infantile onset of symptoms (15.5%, age of onset less than 2 years old, Figure a,b). The majority of patients are diagnosed with dSMA or CMT2D, particularly when the variants are not in the anticodon‐binding or catalytic domain (Chung et al, ; Eskuri et al, ; James et al, ; Liao et al, ) (Figure b). Our identification of three patients with early‐onset SMA adds to the growing appreciation of the broad spectrum of dominant phenotypes associated with GARS pathogenic variants.…”
Section: Resultsmentioning
confidence: 99%
“…Most patients were of adolescent onset, while infant onset was also reported and tended to be more severe [14][15][16]. Severity of phenotype could be varying even in one family [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…CMT2D/dSMA-V typically presents with progressive muscle weakness and atrophy with adolescent or early adult onset (Antonellis et al, 2003); however, a few infantile or early childhood onset cases have been reported (Chae et al, 2015;Chung et al, 2018;Eskuri et al, 2012;James et al, 2006;Liao et al, 2015;Markovitz et al, 2020). Here we report, for the first time, a Chinese family with infantile onset of CMT2D/dSMA-V caused by GARS1 mutation (c.997G>C; NM_002047) probably inherited from mosaic parental germline mutation.…”
Section: Introductionmentioning
confidence: 87%